Imagining communities differently: Print, language and the public sphere in colonial Kerala - Arunima, G (The Indian Economic and Social History Review, 43, 1 (2006), 2006)
This article examines the questions of ethnicity, territoriality and history in Kerala through an examination of two interrelated themes: the emergent print media and its uses, and the problem of language. By looking at examples of primarily two different kinds of prose writing that became available in this period.religious tracts and literary journals (with some references to the more explicitly literary genres like the novel and the short story).it addresses the problem of identity that underlies the changes of the nineteenth and twentieth centuries, and the differential claims that groups made on the public sphere.